Keabsahan dan Kekuatan Hukum Surat Kesepakatan Pengembalian Dana Sebagai Akta di Bawah Tangan Menurut Kitab Undang-Undang Hukum Perdata - Saputra, Agun; S. T. Kansil, Christine (Universitas Ekasakti, 2023)
Service agreements have been known for a long time by the public because they allow easier access to running a business that generally needs to go through a complicated process and takes a long time. This is utilized by parties who have direct access to take care of certain business licenses, for example, the legality of becoming a distributor agent. The problem in this research focuses on the refund agreement letter between Nureni and Ika Jatnika which was made in the form of a deed under the hand. This letter arose because Ika Jatnika had made a default against Nureni. This research is normative legal research using qualitative method. The research legal materials are obtained from literature study and interviews which will be examined with the approach of laws and cases and analyzed qualitatively. The results of this study indicate that the parties are still protected by law because the deed under the hand has valid evidentiary power based on Article 1338 of the Civil Code and the protection of the parties depends on the strength of the type of deed made. The conclusion of this research is that the legal protection of the parties who make a deed under the hand is subject to Article 1338 of the Civil Code and the parties still have the right to claim compensation for material losses they receive.